Complete genome sequence analysis and characterization of selected iron regulation genes of Pasteurella multocida serotype A strain PMTB2.1 - Jabeen, Shagufta; Yap, Huan Yong; Abdullah, Faez Firdaus Jesse; Zakaria, Zunita; Mat Isa, Nurulfiza; Tan, Yung Chie; Yap, Soon Joo; Satharasinghe, Dilan Amila; Omar, Abdul Rahman (MDPI, 2019)
Although more than 100 genome sequences of Pasteurella multocida are available, comprehensive and complete genome sequence analysis is limited. This study describes the analysis of complete genome sequence and pathogenomics of P. multocida strain PMTB2.1. The genome of PMTB2.1 has 2176 genes with more than 40 coding sequences associated with iron regulation and 140 virulence genes including the complete tad locus. The tad locus includes several previously uncharacterized genes such as flp2, rcpC and tadV genes. A transposable phage resembling to Mu phages was identified in P. multocida that has not been identified in any other serotype yet. The multi-locus sequence typing analysis assigned the PMTB2.1 genome sequence as type ST101, while the comparative genome analysis showed that PMTB2.1 is closely related to other P. multocida strains with the genomic distance of less than 0.13. The expression profiling of iron regulating-genes of PMTB2.1 was characterized under iron-limited environment. Results showed significant changes in the expression profiles of iron-regulating genes (p < 0.05) whereas the highest expression of fecE gene (281 fold) at 30 min suggests utilization of the outer-membrane proteins system in iron acquisition at an early stage of growth. This study showed the phylogenomic relatedness of P. multocida and improved annotation of important genes and functional characterization of iron-regulating genes of importance to the bacterial growth.